2016
DOI: 10.1155/2016/9828517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Associative Learning on Memory Spine Formation in Mouse Barrel Cortex

Abstract: Associative fear learning, in which stimulation of whiskers is paired with mild electric shock to the tail, modifies the barrel cortex, the functional representation of sensory receptors involved in the conditioning, by inducing formation of new inhibitory synapses on single-synapse spines of the cognate barrel hollows and thus producing double-synapse spines. In the barrel cortex of conditioned, pseudoconditioned, and untreated mice, we analyzed the number and morphological features of dendritic spines at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Several types of behavioral plasticity are associated with changes in dendritic spines, the primary sites of excitatory synapses in the brain. For example, many forms of learning and memory are accompanied by dendritic spinogenesis (Moser et al, 1994;Leuner et al, 2003;Restivo et al, 2009;Vetere et al, 2011a,b;Bock et al, 2014;Kuhlman et al, 2014;Nishiyama, 2014;González-Tapia et al, 2015Mahmmoud et al, 2015;Jasinska et al, 2016;Ma et al, 2016) or spine elimination (Vetere et al, 2011b;Sanders et al, 2012;Jasinska et al, 2016;Ma et al, 2016;Swanson et al, 2017). Spine plasticity is also associated with proficiency of certain motor tasks (Fu et al, 2012;Liston et al, 2013;Hayashi-Takagi et al, 2015;Gonzalez-Tapia et al, 2016) and potentially, action-outcome expectation, given that drugs that enhance action-outcome learning can trigger spine elimination in certain brain regions (Swanson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several types of behavioral plasticity are associated with changes in dendritic spines, the primary sites of excitatory synapses in the brain. For example, many forms of learning and memory are accompanied by dendritic spinogenesis (Moser et al, 1994;Leuner et al, 2003;Restivo et al, 2009;Vetere et al, 2011a,b;Bock et al, 2014;Kuhlman et al, 2014;Nishiyama, 2014;González-Tapia et al, 2015Mahmmoud et al, 2015;Jasinska et al, 2016;Ma et al, 2016) or spine elimination (Vetere et al, 2011b;Sanders et al, 2012;Jasinska et al, 2016;Ma et al, 2016;Swanson et al, 2017). Spine plasticity is also associated with proficiency of certain motor tasks (Fu et al, 2012;Liston et al, 2013;Hayashi-Takagi et al, 2015;Gonzalez-Tapia et al, 2016) and potentially, action-outcome expectation, given that drugs that enhance action-outcome learning can trigger spine elimination in certain brain regions (Swanson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the possibility that what we observed in cortical L4 is solely the reflection of subcortical changes seems implausible since our experimental paradigm induced many electrophysiological, biochemical, and molecular changes in the cortex. Previously, we found, in barrels representing the trained whiskers in L4, inhibitory synaptogenesis and morphological indices of local protein synthesis in spines, longlasting alterations in NMDA receptor subunit composition, GAD mRNA and protein expression, and changes in neuronal network activity as well as in intrinsic excitability and tonic and phasic GABA currents (Jasinska et al, 2016; for review see Liguz-Lecznar et al, 2016;Siucinska, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Conditioning resulted in an enlargement of the cortical representation of the cognate row of whiskers, as visualized with [ 14 C]-2-deoxyglucose autoradiography (2DG), mainly in cortical layer IV (L4). This plastic change was associated with upregulation of the glutamic acid decarboxylase level in interneurons containing somatostatin (SOM-INs) in L4 of the "trained" whisker representation (Cybulska-Klosowicz et al, 2013b) and with an increased number of inhibitory synapses on double synapse spines in the same location (Jasinska et al, 2016), likely made by SOM-INs (Chiu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The disector method was rapidly adopted by neuroscientists estimating synapse number as serial physical sections are commonly used in transmission electron microscopy and it was well established that synapse size and shape varies with section orientation (Geinisman et al, 1992 , 1996 ). It continues to be a key tool for estimating total synapse number and synapse number per neuron (da Costa et al, 2009 ; Jasinska et al, 2016 ).…”
Section: The Disector Method—a Revolution In the Estimation Of Total mentioning
confidence: 99%
“…Numerous studies have used disector estimates of total synapse number to investigate changes resulting from a number of phenomena including protein undernutrition (Lukoyanov and Andrade, 2000 ), hypothyroidism (Madeira and Paula-Barbosa, 1993 ), aging (Poe et al, 2001 ), epilepsy (Thind et al, 2010 ; Yamawaki et al, 2015 ), diabetes (Zhao et al, 2016 ) and in some cases the reversibility of synapse change (Lukoyanov and Andrade, 2000 ; Yamawaki et al, 2015 ). Studies have also indicated that an increase in the number of synapses occurs with a change in behavior (Klintsova et al, 1997 ; Hajszan et al, 2009 ; Dalzell et al, 2011 ; Jasinska et al, 2016 ). An important aspect of a disector estimate of total synapse number is that values obtained from control animals within any study can be used, due to the unbiased nature of the estimator, by other investigators to model and understand connectivity in the rodent brain (da Costa et al, 2009 ; Ciccarelli et al, 2012 ).…”
Section: Total Number—not Volume or Density—the Pastmentioning
confidence: 99%